Initial Design of Semi Auto Soap Making Device from Used Cooking Oil for Home Appliances - Maidin, N.A.; Rahman, M.H.A.; Ahmad, M.N.; Rahman, S.A.A.; Osman, M.H.; Wahid, M.K.; Alkahari, M.R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This paper presents the comprehensive soap making device that can make soap from used cooking oil. The cooking oil can be converted to soap by using the mixture of used cooking oil, sodium hydroxide (NaOH) pellets, water and scented oil. The experiment was conducted to prove it. By having this right device, it will help users to carry out this converting used cooking oil to become a soap process more easily. They do not need to do this process manually. It can be used at a kitchen in every house. This device designed to raise the awareness the importance of recycling the cooking oil. Surveys has conducted with 50 public respondent, especially house wife. From the survey, it can be concluded that there are many people who dispose the used cooking oil to the place where should not be. The main objective of this paper is to discuss how to design a device to make soap from used cooking oil, to develop a functional prototype of soap making device from used cooking oil for home appliances and also to reduce pollution and increase environmental awareness towards Malaysians.